Histamine Levels in Repeated Thawing Beef - Nurliana Nurliana; Borgo Mauly Nasution; Darmawi Darmawi; Sugito Sugito (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2015)
The aim of this research was to determine the histamine levels in repeated thawing beef. This research were using longisimus dorsi part (sirloin) of beef. Repeated thawing treatments of beef consisted of P1  as control without freezing, P2  as first thawing  after one week freezing, P3  as second thawing without freezing two weeks and P4 with freezing three weeks. The slices of beef was storage in freezer at temperature of -20ºC every weeks for three weeks. The thawing process was done by storage in refrigerator at temperature of 6ºC for 270 minutes after being removed from the storage in freezer every weeks for three weeks. PIC (Protease Inhibiting Cocktail) methode were used to extraction of enzyme in beef. Enzyme Link Imunosorbent Assay (ELISA) were used to detected the histamine levels with 450 nm wave length. The quantitative data from parameters were analyzed by descriptive. The results of the study concluded that repeated thawing beef in refrigerator at temperature of 6ºC could decrease the histamine levels.